Effect of Phytase Enzyme and Diet Type based on Corn or Wheat on Physical Pellet Quality, Growth Performance, Intestinal Morphology and Tibia Characteristics in Broiler Chicks - Mojgan Salmanian; Mahmoud Shams Shargh; Ahad Yamchi; Mohammad Hossein Mohammadi Ghasem Abadi (پژوهشهای تولیدات دامی)
Extended Abstract Background: It is very important to choose the right host for the production of phytase enzyme. Commercial phytase enzymes are produced in bacterial and fungal hosts that can be contaminated with toxic host metabolites. Therefore, to solve this problem, it is recommended to use probiotics as a host. Yeast Saccharomyces boulardi probiotic is a non-pathogenic yeast that does not have the ability to permanently settle in the intestine. The aim of this study was to investigate the effects of two types of commercial phytase (histidine phosphatase group) and recombinant phytase enzymes obtained from Saccharomyces boulardi yeast (purple acid phosphatase group) in corn and or wheat-based diets on pellet physical quality, growth performance, intestinal morphology and tibia characteristics of broiler chicks. Methods: First, the activity level of two types of phytase enzymes was measured and compared by t-test. Then, an experiment was conducted with 4 dietary treatments in the form of a completely randomized design with a factorial arrangement of 2x2, including two types of phytase enzymes (purple acid phosphatase and histidine phosphatase) and two types of diets based on corn or wheat. In this experiment, 336 one-day-old chicks of the Hubbard Flex strain were used in 6 replications (14 birds per each pen). The average body weight gain, feed consumption, feed conversion ratio and European production efficiency factor of experimental treatments were recorded at the age of 10, 24 and 41 days. At the end of the experiment, after starvation and final weighing (41 days old), two male chickens from each experimental unit that had the closest weight to the average of their group were killed to measure the morphological intestine and tibia characteristics. The pellet strength of the final diets of the experimental treatments was also measured by the Holman method. The data were statistically analyzed by Minitab statistical software (version 18) and general linear model procedure. Means compared byTukey's test at 5 percent probability level. Results: The production of recombinant phytase enzyme in the yeast Saccharomyces boulardi probiotic in the fermenter showed that the production efficiency was 400 and 150 grams per liter, respectively, for wet and dry yeast precipitation. Also, measuring phytase enzyme activity showed that the phytase activity in histidine phosphatase was about 2 times higher than of purple acid phosphatase (p≥ 0.05). The effect of the type of diet, the type of phytase enzyme and the interaction between them during different rearing periods in terms of body weight gain (except at the age of ten days), feed consumption, feed conversion ratio and percentage of the European production efficiency index of the whole period, no significant difference was observed. Until the age of ten days, chicks fed by corn-based diet containing histidine phosphatase had the lowest body weight gain compared to chicks fed with corn-based diet containing purple acid phosphatase and wheat-based diet containing histidine phosphatase. The interaction between enzyme and diet type (corn and or wheat) were significant for intestinal morphological characteristics (p≥ 0.05). So, chicks fed corn-based diet with purple acid phosphatase addition had the highest villus surface area and the lowest number of goblet cells in the duodenum and jejunum compared to other experimental treatments (p≥ 0.05). The highest villus length and the ratio of villus length to crypt depth and the lowest crypt depth were observed in the duodenum area of chicks fed corn or wheat-based diets containing purple acid phosphatase compared to other experimental treatments (p≥ 0.05). No statisticall significant difference was observed for the crypt depth in the duodenum and jejunum between the chickens fed by corn or wheat based diet containing purple acid phosphatase. Compared to other experimental treatments, the highest